(untitled) (Research, Society and Development, 2022)
Objectives: The identification of studies that show an approach to spirituality in palliative care in women with cancer, carried out by multidisciplinary and/or interdisciplinary teams in a hospital context. Method: Scoping Review based on the Joanna Briggs Institute’s recommendations and reported by the PRISMA-ScR Extension for Scoping Review. Searches were carried out in six databases, considering the descriptors: women, neoplasms, spirituality, palliative care, patient care, and tertiary health care; there were no restrictions of language or publication year. Results: Of the 801 articles analyzed 4 were included, published from 2014 to 2020. The total number of participants was 1,532, with 733 females and 433 males. Only one study has 366 caregivers/family members as participants, where 62% are female and 38% male. The minimum age ranged from 18 to 21 years. Conclusions: The results indicate that the focus of Spiritual Care (SC) interventions in hospital palliative care was direct attention to the patient and their caregivers/family members, using the following tools: assessment of care needs; care proposal/plan; symptom management/treatment adjustments; health education focused on Spiritual Well-Being (SWB); preparation for death and dignified death. Faced with the complexity of the approach, palliative health professionals need to deepen the discussion about their spirituality in the work environment. It would facilitate understanding of the transcultural nature of religious/spiritual experiences with safety and quality of SC, promoting SWB in cancer patients and their caregivers/family members.